Navigating parental hesitancy in public health: the case for RSV immunization in newborns - Baumgartner, Michael K.; Hanslik, Gregor; Schneider, Mara; Franitza, Manuela; Schneider, Michael; Rieger, Henrike; von Andrian, Hans Christoph; Conrad, Melanie L.; Fahlbusch, Fabian B. (Journal of Perinatology, 2025)
Respiratory syncytial virus (RSV) poses a significant risk to newborns, particularly during the first months of life, and remains a leading cause of pediatric hospitalization in Germany. Despite the approval of innovative immunoprophylaxis methods like nirsevimab, parental hesitancy persists, driven by knowledge gaps and concerns about safety. This study assesses the healthcare burden of RSV during the 2022/2023 and 2023/2024 seasons and explores parental perspectives on immunization just prior to the widespread availability of nirsevimab in late 2024. Data revealed a significant hospital burden, including rising intensive care admissions requiring respiratory support. A survey conducted in two Bavarian maternity wards found that while 78% of parents were aware of RSV, only 53% supported postnatal immunization. These findings highlight the groundbreaking potential of RSV immunization and underscore the urgent need for targeted communication strategies to address parental concerns to ensure successful implementation of these programs.
CRIS-Team Scopus Importer:2025-04-18